If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(x + 2) = (-1x + -4) Reorder the terms: X(2 + x) = (-1x + -4) (2 * X + x * X) = (-1x + -4) (2X + xX) = (-1x + -4) Reorder the terms: 2X + xX = (-4 + -1x) Remove parenthesis around (-4 + -1x) 2X + xX = -4 + -1x Solving 2X + xX = -4 + -1x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: 4 + 2X + x + xX = -4 + -1x + 4 + x Reorder the terms: 4 + 2X + x + xX = -4 + 4 + -1x + x Combine like terms: -4 + 4 = 0 4 + 2X + x + xX = 0 + -1x + x 4 + 2X + x + xX = -1x + x Combine like terms: -1x + x = 0 4 + 2X + x + xX = 0 The solution to this equation could not be determined.
| -2z-2z=6z+1-2z | | x^2+4x+2=9x-4 | | x^2+4x+2=9-4 | | 5x^2+8x-14=40-31x | | 3?(-8)= | | Log(4)(3x-5)=3 | | -6x+7x^2-13= | | 5x^2+30x+29=0 | | -4y+8=-2(4y+4) | | x^2-14x=-7x-6 | | 2In(3x)=8 | | 15x-4+4x+5+65=180 | | x^2-23x+72=-6x | | 5g=2g+12 | | 9p-7p=14 | | 2q^2-9q+5=-3 | | 4/3+4=4/19 | | 4x-6=180 | | 4d^2+4d-2=-3 | | 2lx-6l+14=38 | | 19+8(4-3x)=3(5x+4) | | 6x^2+6x-18=35x+38 | | 20d^2-31d+9=-3 | | -7y=-5x+10 | | 12+2(6+x)=3(x+4) | | y=4.3x | | (-4.25)(2)+(-4.25)(-2)= | | 20d^2-11d-5=-2 | | X(x+2)=-x-4 | | -2x+11x^2-13= | | X-3x^2=49 | | (-4.25)(2)+(-4.25)(2)= |